A translational, caffeine-induced model of onset insomnia in rats and healthy volunteers - Paterson, Louise M.; Wilson, Sue J.; Nutt, David J.; Hutson, Peter H.; Ivarsson, Magnus (Psychopharmacologia, 2007)
Insomnia is a common and disabling complaint for which there is a need for improved treatments. Successful drug discovery relies on the use of appropriate animal models to assess likely outcome in the clinic. The purpose of this study was to develop a translational, caffeine-induced model of insomnia in rats and healthy volunteers. We used sleep onset latency (SOL) as a comparable sleep measure between the two species. The model was validated by two effective sleep-promoting agents with different pharmacology, zolpidem and trazodone, which have GABA-ergic and serotonergic mechanisms, respectively. In rats, radiotelemetry transmitters with electroencephalogram and electromyogram electrodes were implanted for sleep recording. Animals were administered with caffeine alone (10 mg/kg) or in combination with zolpidem (10 mg/kg) or trazodone (20 mg/kg), or vehicle, in crossover experiments. Home polysomnography was performed in 12 healthy male volunteers in a randomised, placebo-controlled, 4-week crossover study. Subjects received placebo, caffeine (150 mg) or caffeine in combination with zolpidem (10 mg) or trazodone (100 mg). Subjective sleep effects in volunteers were assessed using the Leeds Sleep Evaluation Questionnaire. Caffeine caused a significant prolongation in objective SOL in rats and humans. This effect was sensitive to zolpidem and trazodone, both of which attenuated the caffeine-induced increase in SOL. Furthermore, both hypnotics restored the disruption in subjective measures of sleep onset caused by caffeine in volunteers. This model therefore provides a promising paradigm in which we can study novel treatments for sleep disorders and an opportunity for direct comparison of results between rodents and humans.